GE_GERICHTE P/14840/2024 vom 5. März 2025 - GE Cour de justice (2025)
VIOLATION DE DOMICILE;INTERDICTION DE QUITTER UNE RÉGION;SÉJOUR ILLÉGAL;EXEMPTION DE PEINE | CP.186; LEI.115.al1.letb; LEI.119; CP.52; CP.172ter